Digital Interventions as Social Support for Adolescent Psychosocial Development and Educational Policy Malaysia : A Conceptual Review - Muhammad Syafiq Amin, Abdul Hamid; Farah, Zaini; Khalid, Zanudin; Eaqerzilla, Phang; Rochmat Aldy, Purnomo (Penerbit Akademia Baru, 2025)
The Digital Education Policy (DEP) aims to cultivate a generation of digitally fluent individuals who possess knowledge, value studentsandenhance skills and infrastructure across preschool to post-secondary education levels. Previous studies highlight the potential of digital interventions in addressing social issues among adolescents, particularly in providing social support. Despite growing use of digital tools in education, limited research has explored how these technologies can be systematically integrated to provide social and emotional support for adolescents. This gap highlights the need to review existing interventions and their potential for fostering psychosocial development. This review grounded in typological approach prior research—particularly studies conducted in Malaysia—to examine policies concerning the integration of digital technology. The effectiveness of interventions by teachers can influence adolescents' psychosocial well-being in addressing contemporary challenges. Hence, the future research of proposed digital intervention could empirically explore, examine and validate as presented in educational system through implementing nationality education policy.